CURATING THE SELF: BODY IMAGE AND THE AESTHETICS OF LANGUAGE IN YOUTH-CENTRIC INSTAGRAM LITERATURE - Nag, Apoorva Dhara (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This paper explores the intersection of body image, selfhood, and language aesthetics within youth-generated literary content on Instagram, a platform increasingly recognized as a space for digital literature. Drawing upon theoretical frameworks from Judith Butler on performativity and Michel Foucault on discourse and power, the study investigates how young users curate and perform identities through poetic micro-narratives and multimodal compositions. By analyzing Instagram posts that blend minimalist poetry, curated imagery, and strategic paratexts (captions, hashtags), this research reveals how digital aesthetics are used to navigate, affirm, or resist dominant ideals of the body and self-representation. The paper employs qualitative stylistic analysis, supported by critical discourse analysis, to examine how language is used to express vulnerability, resistance, and emotional authenticity. It also addresses the role of visual discourse and ephemeral storytelling in shaping identity construction in online literary spaces. Findings indicate that Instagram literature reflects both a critique of and conformity to prevailing cultural narratives around beauty, gender, and emotional expression, offering a complex field of tension between aesthetic performativity and embodied realities. This study contributes to contemporary literary discourse by expanding the canon to include born-digital youth literature and argues for its legitimacy as a site of serious literary engagement.